ROLAND BARTHERS SEMIOTICS IN THE FILM MENCURI RADEN SALEH BY ANGGA DWIMAS SASONGKO - Hamdah Siti Hamsanah Fitriani; Irpa Anggriani Wiharja (STIBA IEC JAKARTA, 2023)
This study aims to analyze the semiotic theory of Roland Barthers in the film Mencuri Raden Saleh. The aspects that are the focus of this research are the meaning of denotation, connotation and myth contained in the film Mencuri Raden Saleh. This research is a type of qualitative research using content analysis method. The technique for collecting data in this study is the observation and note taking technique. In order to be able to find out in more detail the data used in this study and which were not. The results of this study found that there were 4 types of eating denotations, connotations, and myths in the film Mencuri Raden Saleh. In this film, the use of connotative meaning is very strong, so that in general it is difficult for the audience to find deep meaning in this film